Flood of discoveries in Nepal! - Bhandary, Krishna M (Himalayan Journal of Sciences, 2006)
Access to full text of world’s 7000 leading journals will revalue the role of TUCL.Himalayan Journal of Sciences 1(2): 71, 2003The full text is of this article is available at the Himalayan Journal of Sciences website